2014
DOI: 10.1175/mwr-d-13-00242.1
|View full text |Cite
|
Sign up to set email alerts
|

A GSI-Based Coupled EnSRF–En3DVar Hybrid Data Assimilation System for the Operational Rapid Refresh Model: Tests at a Reduced Resolution

Abstract: A coupled ensemble square root filter-three-dimensional ensemble-variational hybrid (EnSRF-En3DVar) data assimilation (DA) system is developed for the operational Rapid Refresh (RAP) forecasting system. The En3DVar hybrid system employs the extended control variable method, and is built on the NCEP operational gridpoint statistical interpolation (GSI) three-dimensional variational data assimilation (3DVar) framework. It is coupled with an EnSRF system for RAP, which provides ensemble perturbations. Recursive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 79 publications
2
29
0
1
Order By: Relevance
“…For all the Hybrid related experiments in this study, horizontal and vertical localization cut‐off distances (Gaspari and Cohn, ) are 450 km and 1 scale height respectively. The details about converting between the localization length‐scale in the e‐folding distance used in the recursive filter and that in the cut‐off distance used in the method by Gaspari and Cohn () can be found in equation (4) of Pan et al (). These values are selected after tests with a range of values.…”
Section: Experiments Designmentioning
confidence: 99%
“…For all the Hybrid related experiments in this study, horizontal and vertical localization cut‐off distances (Gaspari and Cohn, ) are 450 km and 1 scale height respectively. The details about converting between the localization length‐scale in the e‐folding distance used in the recursive filter and that in the cut‐off distance used in the method by Gaspari and Cohn () can be found in equation (4) of Pan et al (). These values are selected after tests with a range of values.…”
Section: Experiments Designmentioning
confidence: 99%
“…In two-way coupling, additionally ensemble analysis is re-centered to the control hybrid analysis. The two-way coupling implicitly assumes that the hybrid control analysis is better than the ensemble mean analysis, and the re-centering should help to prevent the divergence between the ensemble and hybrid analyses so that the ensemble perturbations can sample the control forecast uncertainty well (Pan et al 2014). In the hybrid configuration we have chosen, ensemble system is not an independent full data assimilation system and ensemble analyses are generated by perturbing control analysis (hybrid analysis).…”
Section: Methodsmentioning
confidence: 99%
“…All observation processing was performed by GSI, and for the EnSRF, GSI generated prior modelsimulated observations for each ensemble member, assigned observation errors, and performed observation thinning and quality control decisions [as in Hamill et al (2011a), SL14, Pan et al (2014), Wang and Lei (2014), Zhu et al (2013), and Kleist and Ide (2015a,b)]. …”
Section: Observationsmentioning
confidence: 99%
“…Ide (2015a), several studies (e.g., Clayton et al 2013;Wang et al 2013;Pan et al 2014;Schwartz et al 2015a) revealed little sensitivity to whether this recentering was performed, which suggests that a single ensemble can safely provide flow-dependent BECs for multiple hybrid experiments (Clayton et al 2013). Thus, based on these collective previous results, EnSRF analyses were not recentered about hybrid analyses, and unless otherwise stated, the same 20-km ensembles provided BECs for all hybrid configurations, which permitted a large number of hybrid experiments to be performed that would have otherwise been impossible (given finite computing resources) had it been necessary to produce new EnSRF analyses for each hybrid experiment.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation